Retroperitoneal alveolar rhabdomyosarcoma intruding into spinal canal: A case report and literature review - Zhang, Yongbai; Huang, Wenpeng; Li, Liming; Qiu, Yongkang; Jiao, Hao; Chen, Zhao; Yang, Qi; Song, Lele; Kang, Lei (Frontiers in Medicine, 2022)
Background Rhabdomyosarcoma (RMS) is the most frequent soft sarcoma in children and adolescents. Alveolar rhabdomyosarcoma (ARMS) is a relatively rare subtype that is characterized by aggressive behavior and an unsatisfactory prognosis. An ARMS can arise anywhere but most commonly occurs at extremity sites with a very small fraction in the retroperitoneum. The utility of 2-Deoxy-2-[fluorine-18]-fluoro-D-glucose (18F-FDG) positron emission tomography combined with computed tomography (PET/CT) remains to be established in ARMS. Case Report A 3-year-old female child was accidentally found with a large left upper abdominal mass for a day. CT examination indicated a huge soft tissue mass in the left retroperitoneum extending superiorly to the level of the left hilus renalis and inferiorly to the left acetabulum in the pelvic cavity, with intrusion into the lumbar foramens. 18F-FDG PET/CT found a mass in the left retroperitoneum from the level of T12 to the left acetabulum, with the maximum standardized uptake value (SUVmax) of about 7.0, and a CT value of about 39 HU, invading the left L3-5 intervertebral foramina and protruding into the spinal canal, with unclear boundary with the spinal cord. Retroperitoneal tumor resection and the repair operation of vascular exploration were performed. An ARMS was confirmed by postoperative biopsy, immunohistochemical staining, and genetic detection with the rupture of the fork head in rhabdomyosarcoma (FKHR). The patient received chemotherapy and was in a good condition with no recurrence and obvious complications. Conclusion Retroperitoneal ARMS is rare and indicates a poor outcome with the potential to involve vital organs and intrude into the spinal canal. Accurate diagnosis and staging using PET/CT would contribute to better risk stratifications and appropriate treatment individually.